2013
DOI: 10.1039/c2ob26707a
|View full text |Cite
|
Sign up to set email alerts
|

A nucleic acid probe labeled with desmethyl thiazole orange: a new type of hybridization-sensitive fluorescent oligonucleotide for live-cell RNA imaging

Abstract: A new fluorescent nucleotide with desmethyl thiazole orange dyes, D'(505), has been developed for expansion of the function of fluorescent probes for live-cell RNA imaging. The nucleoside unit of D'(505) for DNA autosynthesis was soluble in organic solvents, which made the preparation of nucleoside units and the reactions in the cycles of DNA synthesis more efficient. The dyes of D'(505)-containing oligodeoxynucleotide were protonated below pH 7 and the oligodeoxynucleotide exhibited hybridization-sensitive fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A special form of such multicolor probe design consists of co‐labeling a single oligonucleotide with two fluorophores that can engage in energy transfer. Similarly to MB‐FRET, multilabeled ECHO probes, dual‐fluorophore‐labeled PNA FIT, and TO‐JO (oxazolopyridine)‐labeled DNA FIT probes possess greater responsiveness and thus better target discriminating ability, as efficient energy transfer only occurs between bright‐state fluorescent molecules. The high responsiveness of such probes allows wash‐free, single‐step RNA FISH, greatly decreasing the amount of time and labor required to develop the signal—even in large specimens—making these methods ideal tools for high‐throughput quantitative RNA localization studies …”
Section: Fluorogenic Approaches Of In Situ Rna Detectionmentioning
confidence: 99%
“…A special form of such multicolor probe design consists of co‐labeling a single oligonucleotide with two fluorophores that can engage in energy transfer. Similarly to MB‐FRET, multilabeled ECHO probes, dual‐fluorophore‐labeled PNA FIT, and TO‐JO (oxazolopyridine)‐labeled DNA FIT probes possess greater responsiveness and thus better target discriminating ability, as efficient energy transfer only occurs between bright‐state fluorescent molecules. The high responsiveness of such probes allows wash‐free, single‐step RNA FISH, greatly decreasing the amount of time and labor required to develop the signal—even in large specimens—making these methods ideal tools for high‐throughput quantitative RNA localization studies …”
Section: Fluorogenic Approaches Of In Situ Rna Detectionmentioning
confidence: 99%
“…These methods are based on binding of a marker conjugated specific probes on an mRNA in living cells. Recently, techniques involving interaction with small hybridizing sensors been developed (Ikeda et al, ; Okamoto et al, ) and the obtained data revealed the kinetics of mRNA localization as well as spatiotemporal regulation of gene expression in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…TO undergoes forced intercalation upon hybridization of the probe with target RNA, resulting in a significant increase in fluorescence ( Figure 3D ; Bethge et al, 2010). Both ECHO and FIT probes are suitable for in vivo mRNA imaging upon delivery into living eukaryotic cells (Kubota et al, 2009, 2010; Hövelmann et al, 2013, 2014; Okamoto et al, 2013). Interestingly, injection of approximately four FIT probes gives comparable signals as those obtained with the MS2 system in living Drosophila oocytes (Hövelmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%